PISA Achievement in Sweden From the Perspective of Both Individual Data and Aggregated Cross-Country Data - Boman, Björn (Frontiers in Education, 2022)
This study set out to analyze Swedish 15-year-olds’ PISA performance in 2015 and to lesser extent 2018 by using a combination of individual data (2015) and aggregated cross-country data for 2015 and 2018, inclusive of 31 OECD countries. At the within-country and individual level, native Swedish students who took the PISA test in 2015 outperformed first- and second-generation migrants. Moreover, the latent socioeconomic variable “number of books at home” was associated with higher PISA math achievement. Ambition was positively associated with PISA math scores, wheres worry was negatively associated with PISA math. At the cross-country level, GDP per capita was associated with higher PISA scores but ethnic homogeneity was not. IQ scores, PIAAC scores for teachers, and teacher salaries were also moderately correlated with PISA math achievement. This indicates that a country with high cognitive ability levels, as well as cognitively competent and well-paid teachers are likely to perform better in large-scale international assessments such as PISA.